Artificial superintelligence a futuristic approach - Yampolskiy, Roman V., 1979- (CRC Press, 2016)
A day does not go by without a news article reporting some amazing breakthrough in artificial intelligence (AI). Many philosophers, futurists, and AI researchers have conjectured that human-level AI will be developed in the next 20 to 200 years. If these predictions are correct, it raises new and sinister issues related to our future in the age of intelligent machines.